PENANAMAN NILAI MORAL CERITA RAKYAT PERANG OBOR UNTUK MEMBENTUK KARAKTER SISWA - Salsabila Widya Fatina; Puguh Ardianto Iskandar (Universitas Muria Kudus, 2022)
This study aims to identify and describe the moral values that can shape the character of students in the folklore of the Torch War, and to find out how to instill character values in students.The method applied in this research is a qualitative method. The data collection technique in this study was carried out by conducting a literature study. The data sources in this study were journals and folklore of the torch war.Based on the results of the researcher's analysis, the folklore of the torch war contains several moral values contained in it, the value of responsibility, empathy for others, belief in tradition, courage, gratitude towards God, belief in the oneness of God. which can be implemented to shape the character of students. The formation of student character through the folklore of the torch war can be applied in various ways by reading folklore and then students analyze the story, so that indirectly students know the moral values contained therein, these values can later be used as guidelines in carrying out daily activities in environment, then it can be through activities before learning, after learning, and outside of learning, or by teaching good and bad things contained in the values contained in the folklore of the Perang Obor.